2022
DOI: 10.1136/bmjopen-2021-058044
|View full text |Cite
|
Sign up to set email alerts
|

Progression of chronic pain and associated health-related quality of life and healthcare resource use over 5 years after total knee replacement: evidence from a cohort study

Abstract: ObjectiveAs part of the STAR Programme, a comprehensive study exploring long-term pain after surgery, we investigated how pain and function, health-related quality of life (HRQL), and healthcare resource use evolved over 5 years after total knee replacement (TKR) for those with and without chronic pain 1 year after their primary surgery.MethodsWe used data from the Clinical Outcomes in Arthroplasty Study prospective cohort study, which followed patients undergoing TKR from two English hospitals for 5 years. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 44 publications
4
16
0
Order By: Relevance
“…Studies have raised the issue of the bidirectional relationship between pain and sleep [ 40 ]. In line with a previous study [ 41 ], our participants with excessive preoperative pain seemed to experience a cycle of pain and deteriorating health. In addition, poor preoperative sleep quality has been shown to have a negative impact on PPP [ 42 ].…”
Section: Discussionsupporting
confidence: 89%
“…Studies have raised the issue of the bidirectional relationship between pain and sleep [ 40 ]. In line with a previous study [ 41 ], our participants with excessive preoperative pain seemed to experience a cycle of pain and deteriorating health. In addition, poor preoperative sleep quality has been shown to have a negative impact on PPP [ 42 ].…”
Section: Discussionsupporting
confidence: 89%
“…The higher healthcare expenditures in adults with osteoarthritis and pain may be due to chronic pain that may lead to increased utilization of health care resources such as frequent use of outpatient services, pharmacy, and increased emergency department visits. 45,46 This study expanded the previous literature, by determining which of the differences in characteristics contributed to the excess expenditures associated with pain among adults with osteoarthritis using decomposition analysis. In decomposition analysis, we found that nearly two-thirds of the difference in direct healthcare expenditures was explained by differences in predisposing, enabling, need lifestyle, and environmental factors between those with and without pain.…”
Section: Discussionmentioning
confidence: 92%
“…The higher healthcare expenditures in adults with osteoarthritis and pain may be due to chronic pain that may lead to increased utilization of health care resources such as frequent use of outpatient services, pharmacy, and increased emergency department visits. 45 , 46 …”
Section: Discussionmentioning
confidence: 99%
“…The Support and Treatment After Replacement (STAR) care pathway was found to be more clinically effective and cost-effective than usual care for patients with persistent pain at 3 months following pTKA 40 . The natural history of pain following pTKA also appears to be one of improvement over time, with 1 study demonstrating that two-thirds of patients recovered during the first 4 years postoperatively 41 . As such, we caution against early rTKA for unexplained pain.…”
Section: Discussionmentioning
confidence: 99%